Choking – A Public Health Problem- Are We Prepared? - Kumar, Amit; Varshney, Saurabh; Tyagi, Amit Kumar; Patro, Sourabha Kumar; Malhotra, Manu; ., Madhupriya; Bhardwaj, Abhishek (Indian Journal of Community Health, 2019)
Choking or acute airway obstruction is the emergency condition which is usually first dealt by general public and only then by health professionals. It has been documented in literature that educating the public about choking hazards and its management can positively affect the incidence of choking events and mortality. (1) In the developed countries, Basic Life Support (BLS) courses and First Aid courses are routinely done by public and are aggressively pursued by government and health care givers but in India there is no such uniform program. Indian Society of Anesthesiologists (ISA) has developed indigenous CPR guidelines and they are also organizing affordable nationwide CPR training modules, at present their program does not deal with the choking, but hopefully as their program will gain more acceptance, they will also incorporate choking modules. (2) Etiology of choking varies according to the age group and different preventive and management strategies are required for different age groups to tackle this problem. Although data from India is not much, but some common strategies followed by other nations can also be applied to the Indian Population, thus preventing these fatal choking episodes. We hereby discuss this problem according to different age groups and we have made an attempt to recommend some of the preventive strategies in context of Indian scenario Etiology of choking varies according to the age group and different preventive and management strategies are required for different age groups to tackle this problem. We hereby discuss this problem according to different age groups and we have made an attempt to recommend some preventive strategies keeping in mind Indian scenario. Although data from India is not much, but some common strategies which other nations are following can also be applied to the Indian Population, thus preventing these fatal choking episodes.